Handbook of depression : second edition - Friedman, Edward S. (Springer Healthcare Ltd., 2014)
Depression is a common mood disorder that affects approximately 10% of the global population at some point in their lives and can cause serious psychological, physical, and cognitive distress. Additionally, patients with depression are at a greater risk for cardiovascular disease, stroke, functional impairment, disability and all-cause mortality. Aside from the impact on the individual, this condition presents a very real economic burden, as depression is the most predominant mental health problem among working-age patients and the leading cause of lost work productivity. Despite advances in screening and treating depression in recent decades, a vast majority of patients with depression do not actively seek treatment and, of those that do, only a quarter have been found to receive adequate and effective interventions. Handbook of Depression, Second Edition is a concise review of assessment tools, available and emerging pharmacological and non-pharmacological treatment options, and consensus management guidelines that center on enhancing the clinician-patient relationship and improving patient quality of life. Cowritten by expert US- and UK-based authors, this handbook has an innovative global focus that consolidates current knowledge in a convenient, pocket-sized guide that is ideal for every day reference in a clinical setting.